Analysis of Water Chemistry Physics for Fish Cultivation Activities in The Tributary Komering River, Banyuasin District - Elva Dwi Harmilia; Meika Puspitasari; Amin Uswatun Hasanah (Universitas Muhammadiyah Palembang, 2021)
Residents use the Komering tributary that flows through Pangkalan Gelebak Village in Banyuasin Regency for fish farming activities. Villagers tried to cultivate catfish and tilapia, but it did not work because they died. Water as a medium for fish farming activities is an important factor that must be considered. Water quality in waters can affect aquaculture activities and fish growth. The study was conducted to determine the water quality (physics and chemistry) in the Komering River tributary as a basis for the cultivation environment. The research was conducted in the Komering tributary of Pangkalan Gelebak Village, Banyuasin Regency, in September, October, and November 2019. The sampling point is determined using a purposive sampling method in four sampling points. The temperature measurements range from 27-32.7ºC, depth 0.4-9 m, brightness 0.2-1.1 m, and turbidity 12.62-69.2 NTU. Only the depth of the four physical parameters is unsuitable for cultivation activities. During the dry season, the water depth between the riverbed and cage nets does not reach 1m. Chemical parameter measurement results; dissolved oxygen 1.7 – 7 mg/l, pH 6.5 – 7, alkalinity 34 - 46 mg/l CaCO3, nitrate 0.892 - 2.278 mg/l, nitrite 0.032 - 0.217 mg/l, ammonia 0.02-0.398 mg/ l and ortho-phosphate 0.054-0.283 mg/l. The value of nitrate, ammonia, and orthophosphate indicated high values so than unsuitable for fish farming activities. Agricultural activities around creeks and domestic waste disposal are causes of poor water quality.